2014
DOI: 10.1186/preaccept-2085133501150912
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia: a too long unfairly neglected major cardiovascular risk factor

Abstract: The existence of an independent association between elevated triglyceride (TG) levels, cardiovascular (CV) risk and mortality has been largely controversial. The main difficulty in isolating the effect of hypertriglyceridemia on CV risk is the fact that elevated triglyceride levels are commonly associated with concomitant changes in high density lipoprotein (HDL), low density lipoprotein (LDL) and other lipoproteins. As a result of this problem and in disregard of the real biological role of TG, its significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 126 publications
(131 reference statements)
1
51
0
Order By: Relevance
“…TG, as far as is currently known, is not directly atherogenic but represent an important biomarker of CVD risk because of its association with atherogenic remnant particles and apo C-III, a proatherogenic protein found on all classes of the plasma lipoproteins [31]. A recent review suggested that TG may also stimulated atherogenesis by other mechanisms, which included the production of proinflammatory cytokines, fibrinogen and coagulation factors and impairment of fibrinolysis [32]. In our study, we did find a significant increase in TG levels in subjects with subclinical atherosclerosis, but the precise role of TG in the pathogenesis of atherosclerosis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…TG, as far as is currently known, is not directly atherogenic but represent an important biomarker of CVD risk because of its association with atherogenic remnant particles and apo C-III, a proatherogenic protein found on all classes of the plasma lipoproteins [31]. A recent review suggested that TG may also stimulated atherogenesis by other mechanisms, which included the production of proinflammatory cytokines, fibrinogen and coagulation factors and impairment of fibrinolysis [32]. In our study, we did find a significant increase in TG levels in subjects with subclinical atherosclerosis, but the precise role of TG in the pathogenesis of atherosclerosis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…The HDL cholesterol hypothesis is gradually being replaced by the HDL function hypothesis [34]. HDL cholesterol might be a marker of cardiovascular health but is non-causal in the atherogenesis [32,34]. Currently LDL is considered as the major atherogenic lipoprotein [32], it is a heterogeneous class of particles and accumulating evidence suggests that different LDL subfractions vary in their risk profile [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the association of higher T with lower TG in community-dwelling men (Group A), this may be mediated via the relationship between higher T and more favourable body composition [30,31]. High TG has been associated with reduced HDL, increased small dense LDL, production of proinflammatory cytokines, endothelial dysfunction, and thereby with increased cardiovascular risk [32].…”
Section: Associations Of Sex Hormones With Carotid Plaquementioning
confidence: 99%
“…The result of 29 prospective studies analysis showed that patients in the highest versus the lowest tertile of triglyceride had an odds ratio of 1.72 for CHD (95% CI, 1.56-1.90). (7,12) In patients with very high triglyceride levels and patients with familial chylomicronemia syndrome the risk for atherosclerosis is attenuated, maybe since their plasma lipoprotein particles are too large to enter into the arterial intima. Nevertheless, there are many indications that there is an increased risk of CV disease in the marked or severe HTG as well.…”
Section: Serum Triglycerides As Risk Factor For Cardiovascular Diseasementioning
confidence: 99%